2018
DOI: 10.1111/epi.14019
|View full text |Cite
|
Sign up to set email alerts
|

The immediate and short‐term effects of bilateral intrahippocampal depth electrodes on verbal memory

Abstract: In contrast to previous studies, Ljung et al. provide evidence of permanent cognitive consequences of bilateral intrahippocampal depth electrodes for verbal memory in patients who were not operated or operated in the right temporal lobe. Stimulated by this, we provide historical confirmatory and supplementary evidence of the detrimental effect of bilateral depth electrodes implanted along the longitudinal axis of the hippocampus on verbal learning and especially on delayed verbal memory and recognition perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…Helmstaedter et al from Bonn University in Germany conducted a retrospective study from data collected in the late 1990s to assess the immediate and short‐term effects of bilateral hippocampal depth electrodes on verbal memory. Electrodes were implanted along the longitudinal axis of the hippocampus in 31 patients, and memory assessments were obtained before implantation, shortly after explantation, and 3 months after temporal lobe epilepsy (TLE) surgery (left = 21, right = 10).…”
Section: Two Studies Raising New Concernsmentioning
confidence: 99%
See 4 more Smart Citations
“…Helmstaedter et al from Bonn University in Germany conducted a retrospective study from data collected in the late 1990s to assess the immediate and short‐term effects of bilateral hippocampal depth electrodes on verbal memory. Electrodes were implanted along the longitudinal axis of the hippocampus in 31 patients, and memory assessments were obtained before implantation, shortly after explantation, and 3 months after temporal lobe epilepsy (TLE) surgery (left = 21, right = 10).…”
Section: Two Studies Raising New Concernsmentioning
confidence: 99%
“…Visual memory was not reported. The authors concluded that their data “provide historic confirmatory and supplementary evidence of the detrimental effect of bilateral depth electrodes implanted along the longitudinal axis of the hippocampus on verbal learning.” Based on their findings, the Bonn group “restricted implantations to one hippocampus if ever possible” and later switched to “stereotactic implantations with lateral depth‐electrodes, placed orthogonally to the long axis of the hippocampus.”…”
Section: Two Studies Raising New Concernsmentioning
confidence: 99%
See 3 more Smart Citations